Social disequilibrium, distributive inequality and unemployment in Peru, 2004 - 2017 - Ávalos, Eloy (2024)
The main objective of this paper is to contrast an extension of the hypothesis of the distributive imbalance theory formulated by Figueroa (1993, 2015). To achieve the objective, two indices were constructed; one that measures social disorder and another that measures distributive inequality. Then, the panel data econometric technique under random effects was used, having as empirical units of analysis the departments of Peru for the period 2004-2017. The results achieved in the present investigation show that a relationship between social disorder and the unemployment rate; as well as between distributive inequality and social imbalance, has empirical support and are in accordance with what is expected according to the formulations of the economic theory based on economic envy and the limits of tolerance to distributive inequality.